2019
DOI: 10.1016/j.abd.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Extensive pyoderma gangrenosum-like lesions revealing a case of hyperzincemia and hypercalprotectinemia: when to suspect it?

Abstract: Hyperzincemia and hypercalprotectinemia is a rare inflammatory disease caused by a mutation in the PSTPIP1 gene, with a dysregulation of calprotectin metabolism. Calprotectin is a zinc-binding protein with antimicrobial properties and pro-inflammatory action. The authors report the case of a 20 year-old girl with cutaneous ulcers comparable with pyoderma gangrenosum, growth failure and chronic anemia, who was given the diagnosis of hyperzincemia and hypercalprotectinemia. Measurement of serum zinc and calprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Hyperzincaemia and hypercalprotectinaemia (also known as PSTPIP1-associated myeloid-related proteinemia inflammatory syndrome) is characterized by severe systemic and cutaneous inflammation, hepatosplenomegaly, arthritis, pancytopenia and failure to thrive owing to the accumulation of zinc 79 . Dermatological symptoms share clinical and histopathological similarities to pyoderma gangrenosum and include vasculitis, furuncle-like ulcers, and eczematous and necrotic lesions that typically affect the lower limbs symmetrically, although eyelids may also be involved 80 . In contrast to PAPA, the hyperzincaemia and hypercalprotectinaemia/PSTPIP1-associated myeloid-related proteinemia inflammatory phenotype has only been associated with a single amino acid change in PSTPIP1, altering the electrostatic potential and enhancing binding to pyrin 79 .…”
Section: Aetiology Of Autoinflammatory Diseasesmentioning
confidence: 99%
“…Hyperzincaemia and hypercalprotectinaemia (also known as PSTPIP1-associated myeloid-related proteinemia inflammatory syndrome) is characterized by severe systemic and cutaneous inflammation, hepatosplenomegaly, arthritis, pancytopenia and failure to thrive owing to the accumulation of zinc 79 . Dermatological symptoms share clinical and histopathological similarities to pyoderma gangrenosum and include vasculitis, furuncle-like ulcers, and eczematous and necrotic lesions that typically affect the lower limbs symmetrically, although eyelids may also be involved 80 . In contrast to PAPA, the hyperzincaemia and hypercalprotectinaemia/PSTPIP1-associated myeloid-related proteinemia inflammatory phenotype has only been associated with a single amino acid change in PSTPIP1, altering the electrostatic potential and enhancing binding to pyrin 79 .…”
Section: Aetiology Of Autoinflammatory Diseasesmentioning
confidence: 99%
“…Our review identified 252 articles through database searches. After eliminating duplicates and excluding unqualified articles, we included 25 relevant articles that described 43 patients with PAMI syndrome [ 1 , 2 , 3 , 5 , 6 , 7 , 8 , 9 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…While primarily affecting these areas, our review highlighted that other organs may also be affected considerably. Several authors have reported gastrointestinal involvement, with 16% of cases experiencing flare-ups of colitis and/or chronic diarrhea [ 3 , 16 , 19 , 20 , 24 , 28 , 29 ]. Notably, 57% of these patients developed the disease within the first few months of life, suggesting that PAMI syndrome should be considered in the differential diagnosis of early onset inflammatory bowel disease (IBD).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation